Diclofenac-Induced Apoptosis in the Neuroblastoma Cell Line SH-SY5Y: Possible Involvement of the Mitochondrial Superoxide Dismutase. (17th June 2010) - Cecere, Francesca; Iuliano, Annarita; Albano, Francesco; Zappelli, Claudia; Castellano, Immacolata; Grimaldi, Pasquale; Masullo, Mariorosario; De Vendittis, Emmanuele; Ruocco, Maria Rosaria
Abstract : Diclofenac, a nonsteroidal anti-inflammatory drug, induces apoptosis on the neuroblastoma cell line SH-SY5Y through a mitochondrial dysfunction, affecting some antioxidant mechanisms. Indeed, the time- and dose-dependent increase of apoptosis is associated to an early enhancement of the reactive oxygen species (ROS). Mitochondrial superoxide dismutase (SOD2) plays a crucial role in the defence against ROS, thus protecting against several apoptotic stimuli. Diclofenac decreased the protein levels and the enzymatic activity of SOD2, without any significant impairment of the corresponding mRNA levels in the SH-SY5Y extracts. When cells were incubated with an archaeal exogenous thioredoxin, an attenuation of the diclofenac-induced apoptosis was observed, together with an increase of SOD2 protein levels. Furthermore, diclofenac impaired the mitochondrial membrane potential, leading to a release of cytochrome c . These data suggest that mitochondria are involved in the diclofenac-induced apoptosis of SH-SY5Y cells and point to a possible role of SOD2 in this process.